Frequency of celiac disease in patients with vitiligo - Sunu, Cenk; Varim, Ceyhun; Karacaer, Cengiz; Kalpakci, Yasin (International Journal of Advances in Medicine, 2020)
Background: Celiac disease (CD) is an autoimmune and inflammatory disease that occurs in the small intestine as a result of gluten intake in individuals. Vitiligo, in which autoimmune factors play an essential role, is associated with depigmentation due to the loss of epidermal melanocytes. Many autoimmune diseases are known to be associated with vitiligo. This study aims to determine the frequency of CD in vitiligo cases. Methods: Out of 61 vitiligo patients, 32 (52.4%) are women, and 29 (47.6%) are men; of the 119 healthy volunteers, 58 (48.7%) are women, and 61 (51.3%) are men. Serum levels of tissue transglutaminase (tTG) IgA and tTG IgG antibodies were measured in all participants. If at least one of these two antibodies are positive, mucosal biopsies were taken from the second section of the duodenum by endoscopy. Results: There is no significant difference between the study group and the control group in terms of age and body mass index (BMI) (p=0.16, p=0.80, respectively). tTG IgA and tTG IgG were positive in one patient in each group. In both patients, the results of the duodenal biopsy were histopathological compatible with CD. There was no difference between the vitiligo group and the control group in terms of CD frequency (p=0.56). Conclusion: The frequency of CD in vitiligo patients is similar to the control group. However, it should be kept in mind that the frequency of CD in patients with vitiligo may be higher than the rates assumed incidental, and necessary research should be carried out for early diagnosis in such patients.